Development and optimization of polystyrene nanoparticle templated optical fiber platform for in vivo surface enhanced Raman spectroscopy. - Low, Vway Hau. (2011)
The report presents the development and optimization of a new class of Surface Enhanced Raman Scattering (SERS) based optical fiber sensing platform known as metal-film over nanospheres (MFON) SERS active fiber. It involved deposition of polystyrene (PS) nanospheres, followed by silver (Ag) film coating. Morphological characterization of the SERS active surfaces was conducted using Scanning Electron Microscopy (SEM) and the SERS performances of the fibers were evaluated by studying the signal intensity measured from analyte molecules through a backscattering geometry. Through a comparative analysis, the novel MFON SERS active fiber was proved to have SERS enhancement ability of 25 fold more than the reported gold nanoparticles immobilized SERS active fiber. Two novel methods have been proposed to deposit the PS nanospheres monolayer on the fiber tip, including a simple ‘dip and dry’ method and PS nanospheres anchoring using chemical method. Optimization of the SERS active fibers was done by varying the PS size, PS concentration and Ag film thickness to search for the best configuration that is able to contribute to high SERS enhancement at the same time achieve a good sample-to-sample reproducibility.